Carbon isotopic composition of Neoproterozoic glacial carbonates as a test of paleoceonographic models for snowball Earth phenomena - Kennedy, Martin J.; Christie-Blick, Nicholas; Prave, Anthony R. (2001)
Consistently positive carbon isotopic values were obtained from in situ peloids, ooids, and stromatolitic carbonate within Neoproterozoic glacial successions in northern Namibia, central Australia, and the North American Cordillera. Because positive values continue upward into the immediately overlying postglacial cap carbonates, the negative isotopic excursions widely observed in those carbonate rocks require an explanation that involves a short-term perturbation of the global carbon cycle during deglaciation. The data do not support the ecological consequences of complete coverage of the glacial ocean with sea ice, as predicted in the 1998 snowball Earth hypothesis of P.F. Hoffman et al. In the snowball Earth hypothesis, the postglacial cap carbonates and associated -5% negative carbon isotopic excursions represent the physical record of CO 2 transfer from the high-pCO 2 snowball atmosphere (~0.12 bar) to the sedimentary reservoir via silicate weathering in the snowball aftermath. Stratigraphic timing constraints on cap carbonates imply weathering rates of ~1000 times preglacial levels to be consistent with the hypothesis. The absence of Sr isotopic variation between glacial and postglacial deposits and calculations of maximum weathering rates do not support a post-snowball weathering event as the origin for cap carbonates and associated isotopic excursions.